An exploration of the cognitive processes of design teams to inform design education and practice - Kiernan, Louise; Ledwith, Ann; Lynch, Raymond (Design and Technology Education: An International Journal, 2022)
While design is associated with novelty and creativity, few studies have explored the cognitive processes employed during team interactions. Design practice is collaborative where designers work in multidisciplinary teams. Along with the cognitive skills involved in designing, designers also need skills to work in teams, share information, and negotiate decisions. The aim of this study is to understand the cognitive processes used by design teams during the early phases of product design. This study uses case studies and applies content analysis to examine the conversations of design teams during the problem definition, ideation, and concept development phases of the design process. Creativity has been described in terms of sudden bursts of ideas described as creative leaps and is associated with creative thinking. The findings in this study shows that while creative thinking is essential to creative teams, other cognitive modes such as knowledge processing, critical thinking, and metacognition are engaged in more frequently. The emphasis of each cognitive process also varies depending on the phase of the design process. These findings have implications for how design students are educated, the skills required and how we promote creativity in design teams.